Effective Nursing Rounding Significantly Improves Patient Experience and Nurse Job Satisfaction - Romlah Asanah; Asnet Leo Bunga; Evra Yusandra Arifin (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
The implementation of nursing rounding is a routine nurse visitation conducted to evaluate patients’ conditions and ensure that their needs are consistently met. This intervention also strengthens the empathic relationship between nurses and patients through full presence, direct communication, and patient-centered attention. This study aimed to analyze the effectiveness of nursing rounding implementation on patient and nurse satisfaction levels. A quasi-experimental design with a one-group posttest approach was employed to evaluate patient satisfaction, nurse satisfaction, and the implementation of nursing rounding through observational methods. Nursing rounding interventions were conducted every two hours for hospitalized patients. The study was carried out in the Inpatient Unit of Hospital X in January 2026, involving 60 hospitalized patients and 35 nurses. Data were collected using demographic questionnaires, nursing rounding observation sheets, the Patient Reported Experience Measures (PREMS) questionnaire, and the McCloskey/Mueller Satisfaction Scale (MMSS). Patient and nurse satisfaction were measured after the intervention using questionnaires and subsequently analyzed using parametric statistical tests. The results showed that the majority of nurses were aged 26–35 years (60.0%), held professional nursing (ners) qualifications (54.3%), and were at pk i clinical level (77.1%). Meanwhile, most patients were aged 26–35 years (31.7%), female (53.3%), and employed (66.7%). Following the implementation of nursing rounding, most nurses reported satisfaction within the satisfied category, while most patients were categorized as very satisfied. Statistical analysis demonstrated that nursing rounding implementation had a significant effect on both nurse satisfaction (p-value = 0.000) and patient satisfaction (p-value = 0.000). In conclusion, nursing rounding implementation was identified as a primary contributing factor to both patient and nurse satisfaction.Keywords: nursing rounding implementation; nurse job satisfaction; patient experience